 6.3. FUNCOID AS CONTINUATION

102

Theorem

595

.

Fix sets

A

and

B

. Let

L

F

=

λf

FCD

(

A

;

B

) :

h

f

i

and

L

R

=

λf

FCD

(

A

;

B

) :[

f

]

.

1

.

L

F

is a bijection from the set

FCD

(

A

;

B

) to the set of functions

α

F

(

B

)

P

A

that obey the conditions (for every

I, J

P

A

)

α

= 0

F

(

B

)

,

α

(

I

B

) =

αI

t

αJ.

(3)

For such

α

it holds (for every

X ∈

F

(

A

))

L

1

F

α

X

=

l

h

α

i

X

.

(4)

2

.

L

R

is a bijection from the set

FCD

(

A

;

B

) to the set of binary relations

δ

P

(

P

A

×

P

B

) that obey the conditions

¬

(

I δ

)

,

I

J δ K

I δ K

J δ K

(for every

I, J

P

A

,

K

P

B

)

,

¬

(

δ I

)

,

K δ I

J

K δ I

K δ J

(for every

I, J

P

B

,

K

P

A

)

.

(5)

For such

δ

it holds (for every

X ∈

F

(

A

),

Y ∈

F

(

B

))

X

L

1

R

δ

Y ⇔ ∀

X

∈ X

, Y

∈ Y

:

X δ Y.

(6)

Proof.

Injectivity of

L

F

and

L

R

, formulas (

4

(for

α

im

L

F

) and (

6

(for

δ

im

L

R

), formulas (

3

and (

5

follow from two previous theorems. The only

thing remained to prove is that for every

α

and

δ

that obey the above conditions a

corresponding funcoid

f

exists.

2

Let define

α

F

(

B

)

P

A

by the formula

(

αX

) =

Y

P

B

XδY

for every

X

P

A

. (It is obvious that

Y

P

B

XδY

is a free star.) Analogously it can be

defined

β

F

(

A

)

P

B

by the formula

(

βY

) =

X

P

A

XδY

. Let’s continue

α

and

β

to

α

0

F

(

B

)

F

(

A

)

and

β

0

F

(

A

)

F

(

B

)

by the formulas

α

0

X

=

l

h

α

i

X

and

β

0

Y

=

l

h

β

i

Y

and

δ

to

δ

0

by the formula

X

δ

0

Y ⇔ ∀

X

∈ X

, Y

∈ Y

:

X δ Y.

Y u

α

0

X 6

=

F

(

B

)

⇔ Y u

d

h

α

i

X 6

=

F

(

B

)

d

hYui

h

α

i

X 6

=

F

(

B

)

. Let’s

prove that

W

=

hYui

h

α

i

X

is a generalized filter base: To prove it is enough to show that

h

α

i

X

is a

generalized filter base. If

A

,

B ∈ h

α

i

X

then exist

X

1

, X

2

∈ X

such that

A

=

αX

1

,

B

=

αX

2

.

Then

α

(

X

1

X

2

)

∈ h

α

i

X

. So

h

α

i

X

is a generalized filter base and thus

W

is a generalized filter base.

By properties of generalized filter bases,

d

hYui

h

α

i

X 6

=

F

(

B

)

is equivalent

to

X

∈ X

:

Y u

αX

6

=

F

(

B

)

,

what is equivalent to

X

∈ X

, Y

∈ Y

:

B

Y

u

αX

6

=

F

(

B

)

X

∈ X

, Y

∈ Y

:

Y

(

αX

)

X

∈ X

, Y

∈ Y

:

X δ Y.

Combining the equivalencies we get

Y u

α

0

X 6

=

F

(

B

)

⇔ X

δ

0

Y

. Analogously

X u

β

0

Y 6

=

F

(

A

)

⇔ X

δ

0

Y

. So

Y u

α

0

X 6

=

F

(

B

)

⇔ X u

β

0

Y 6

=

F

(

A

)

, that is

(

A

;

B

;

α

0

;

β

0

) is a funcoid. From the formula

Y u

α

0

X 6

=

F

(

B

)

⇔ X

δ

0

Y

it follows

that

X

[(

A

;

B

;

α

0

;

β

0

)]

Y

⇔↑

B

Y

u

α

0

A

X

6

=

F

(

B

)

⇔↑

A

X δ

0

B

Y

X δ Y.